2011
DOI: 10.1007/s10916-011-9721-2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Physical Activity: A Study of Self-Revelation in an Online Community

Abstract: The importance of regular physical activity to overall health has been well established, yet adults in the United States are leading increasingly sedentary lives. Research suggests that lowering perceived barriers to exercise is an effective strategy for encouraging physical activity. This article describes the top barriers that emerged from a qualitative analysis of message board traffic from a threemonth healthy lifestyle intervention that promoted physical activity and healthy eating. The findings further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 39 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…Our participants experienced many of the same barriers and facilitators of behavioral change as those identified by members of the general population (Hammarstrom, Wiklund, Lindahl, Larsson, & Ahlgren, 2014;Ruelaz et al, 2007;Shuval et al, 2013;Toscos, Consolvo, & McDonald, 2011), though we also identified barriers that appear more significant for individuals with serious mental illnesses or that may interact with psychiatric symptoms to make lifestyle changes more difficult to adopt or sustain.…”
Section: Discussionmentioning
confidence: 64%
“…Our participants experienced many of the same barriers and facilitators of behavioral change as those identified by members of the general population (Hammarstrom, Wiklund, Lindahl, Larsson, & Ahlgren, 2014;Ruelaz et al, 2007;Shuval et al, 2013;Toscos, Consolvo, & McDonald, 2011), though we also identified barriers that appear more significant for individuals with serious mental illnesses or that may interact with psychiatric symptoms to make lifestyle changes more difficult to adopt or sustain.…”
Section: Discussionmentioning
confidence: 64%
“…The interactive online message board provides a mechanism through which participants can share their own physical activity experience and receive support/coaching from peers and healthcare providers. 56,57 The message board consists of a discussion board, multimedia upload functions (as in Facebook), and physical activity log functions, with daily monitoring by an RN under the supervision of a family physician. Interactive online educational sessions (users can choose the contents and ask questions and/or provide feedback by clicking buttons on the menu) provide information/knowledge about topics related to the three modifiable factors.…”
Section: Componentsmentioning
confidence: 99%
“…SCD predominantly occurs during periods of medium-low oxygen demand such as during the warm up and inactive periods of matches [31]. Despite the severity of SCD, there is still great debate about the complex aetiological pathways involved [48,49] and the definition of SCD varies between studies [50].…”
Section: Risks Associated With Increasing Physical Activity Levels Sumentioning
confidence: 99%
“…The origin of SCD in older athletes (>35) however is caused by myocardial infarctions secondary to underlying coronary artery disease in the majority of cases [49].…”
Section: Risks Associated With Increasing Physical Activity Levels Sumentioning
confidence: 99%